Microfracture Augmentation With Direct In Situ Radial Shockwave Stimulation With Appropriate Energy Has Comparable Repair Performance With Tissue Engineering in the Porcine Osteochondral Defect Model - Zhidong Zhao; Ji Li; Xiaowei Bai; Yuxing Wang; Qi Wang; Ningyu Lv; Huayi Gao; Zheng Guo; Heng Zhu; Quanyi Guo; Zhongli Li (SAGE Journals, 2022)
Background:
The first-line clinical strategy for small cartilage/osteochondral defects is microfracture (MF). However, its repair efficacy needs improvement.
Hypothesis:
Appropriate energy radial shockwave stimulation in MF holes would greatly improve repair efficacy in the porcine osteochondral defect model, and it may obtain comparable performance with common tissue engineering techniques.
Study Design:
Controlled laboratory study.
Methods:
Osteochondral defect models (8-mm diameter, 3-mm depth) were established in the weightbearing area of Bama pigs’ medial femoral condyles. In total, 25 minipigs were randomly divided into 5 groups: control (Con; without treatment), MF, MF augmentation (MF+; treated with appropriate energy radial shockwave stimulation in MF holes after MF), tissue engineering (TE; treated with compounds of microcarrier and bone marrow mesenchymal stem cells), and sham (as the positive control). After 3 months of intervention, osteochondral specimens were harvested for macroscopic, radiological, biomechanical, and histological evaluations. The statistical data were analyzed using 1-way analysis of variance.
Results:
Based on the macroscopic appearance, the smoothness and integration of the repaired tissue in the MF+ group were improved when compared with the Con and MF groups. The histological staining suggested more abundant cartilaginous matrix deposition in the MF+ group versus the Con and MF groups. The general scores of the macroscopic and histological appearances were comparable in the MF+ and the TE groups. The high signal areas of the osteochondral unit in the magnetic resonance images were significantly decreased in the MF+ group, with no difference with the TE group. The micro–computed tomography data demonstrated the safety of direct in situ radial shockwave performance. Biomechanical tests revealed that the repaired tissue’s Young modulus was highest in the MF+ group and not statistically different from that in the TE group.
Conclusion:
Direct in situ radial shockwave stimulation with appropriate energy significantly improves the short-term repair efficacy of MF. More encouragingly, the MF+ group in our study obtained repair performance comparable with the TE therapy.
Clinical Relevance:
This strategy is easy to perform and can readily be generalized with safety and higher cartilage repair efficacy. Moreover, it is expected to be accomplished under arthroscopy, indicating tremendous clinical transformative value.
Keywords: Orthopaedics; Sports Medicine; Surgery